2021
DOI: 10.3389/fpubh.2021.611652
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Incidence Rate of Diabetes, Pre-diabetes, Uncontrolled Diabetes, and Their Predictors in the Adult Population in Southeastern Iran: Findings From KERCADR Study

Abstract: Background: Diabetes mellitus is among the most serious health challenges worldwide. We assessed the prevalence of pre-diabetes (pre-DM) and diabetes (DM), the effectiveness of diabetes management, the 5-year incidence rate, and associated variables in the adult population in southeastern Iran.Methods: In a random cluster household survey (2014–2018), 9,959 adult individuals aged 15–80 years were assessed for coronary artery disease risk factors, including diabetes mellitus in Kerman (KERCADRS, phase 2). Among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 38 publications
4
21
2
Order By: Relevance
“…Tis study is in line with our current study that found a high prevalence of obesity among the subjects. Te signifcant increase in the prevalence of prediabetes has also been reported in England, the US, Iran, and Turkey [24][25][26][27]. Age, BMI, health insurance ownership, history of hypertension and gout, and systolic blood pressure were found to be signifcantly associated with prediabetes in the present study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Tis study is in line with our current study that found a high prevalence of obesity among the subjects. Te signifcant increase in the prevalence of prediabetes has also been reported in England, the US, Iran, and Turkey [24][25][26][27]. Age, BMI, health insurance ownership, history of hypertension and gout, and systolic blood pressure were found to be signifcantly associated with prediabetes in the present study.…”
Section: Discussionsupporting
confidence: 81%
“…This study is in line with our current study that found a high prevalence of obesity among the subjects. The significant increase in the prevalence of prediabetes has also been reported in England, the US, Iran, and Turkey [ 24 27 ].…”
Section: Discussionmentioning
confidence: 87%
“…This cross‐sectional study was a sub‐analysis of 1033 subjects who participated in the second phase of the Kerman Coronary Artery Disease Risk Factor Study (KERCADRS) 17 . The sampling method was a cluster from the entire population of Kerman residents.…”
Section: Methodsmentioning
confidence: 99%
“…None of the included participants had a history of chronic infectious or inflammatory diseases or the use of any drugs known to affect haematological parameters or lipoprotein metabolism. More details about the data collection method have been published in the study of Najafipour et al 17 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation